EL CUENTO FANTÁSTICO COMO ESTRATEGIA DIDÁCTICA PARA REFORZAR EL APRENDIZAJE DE CONCEPTOS SEMIÓTICOS EN ESTUDIANTES DE LA CARRERA DE DISEÑO GRÁFICO - Jiménez-Álvaro, Xavier Fernando (2025)
AbstractThis educational research article, with a quasi-experimental, pretest–posttest design in a single group, analyzes the impact of the fantastic tale as a teaching strategy for reinforcing understanding of theoretical semiotic concepts among fourth-semester Graphic Design students at the Pontifical Catholic University of Ecuador (PUCE, Quito campus). Fifteen students participated; after taking a pretest on five semiotic notions (sign, denotation/connotation, meaning/signifier, syntagm/paradigm, icon/index/symbol), they read and analyzed the original story Ciudad sin Fondo (Bottomless City), structured according to Freytag’s pyramid and the Hero’s Journey. Subsequently, they carried out comprehension and schematization activities, followed by an equivalent posttest with variations in the questions. Comparative analysis revealed significant improvements in multiple-choice items (+35%) and matching items (+21%), with notable strengthening of denotation/connotation (+44%) and definition of sign (+19%). However, in open-ended questions, the overall average remained stable (-2%), indicating persistent difficulties in the precise verbalization of closely related concepts such as meaning/signifier and icon/index/symbol. The study concludes that narrative fosters the identification and contextual understanding of semiotic concepts, though it must be complemented with activities aimed at terminological and argumentative formalization. It is recommended to integrate visual resources and generative artificial intelligence to optimize working time and enhance the theoretical application in meaningful graphic representations. Keywords: Applied semiotics, design pedagogy, fantasy story (storytelling), meaningful learning,graphic design.